Save Our Senior Noncitizens: Extending Old Age Assistance to Immigrants in the United States, 1935–71. Issue 1 (3rd December 2021) - Fox, Cybelle
Abstract: When do states grant social rights to noncitizens? I explore this question by examining the extension of Old Age Assistance (OAA) to noncitizens after the passage of the 1935 Social Security Act. While the act contained no alienage-based restrictions, states were permitted to bar noncitizens from means-tested programs. In 1939, 31 states had alienage restrictions for OAA. By 1971, when the Supreme Court declared state-level alienage restrictions unconstitutional, only eight states still did. States with more Mexicans and Asians were slower to repeal restriction, however. Using in-depth case studies of New York, California, and Texas, I demonstrate the importance of federal and state institutional arrangements and immigrant political power for the extension of social rights to noncitizens. I also show that to secure access to OAA, immigrant advocates adapted their strategies to match the institutional and political context.